The Effect of Disaster Information in Online Media - Nefianto, Tirton; Wijayanto, Joni; Sinisuka, Meiwana (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2016)
This research aims to measure the level of disaster preparedness and analyze disaster information in the online media on the level of preparedness Jakarta Capital City. This study uses a mix methods. Data were obtained from questionnaires and interviews. The results showed that the average level of disaster preparedness in teenagers were categorized medium, i.e. 63.78. Qualitative analysis of the results of the data collection is known that online media affect the improvement of disaster preparedness, but teenagers at State Junior High 3 Jakarta online media as a tool not optimally used.